DISASTER ASSISTANCE MANAGEMENT OF MERAPI VOLCANO ERUPTION IN 2010 - Ari Saptoto, Sarastomo (Jurnal Ilmiah Administrasi Publik, 2015)
Disaster Assistance Management Of Merapi Volcano Eruption In 2010. This study discusses the disaster assistance management in Sleman Regency, Yogyakarta Special Region Province, particularly at the time of the eruption of Merapi Volcano in 2010. This study used descriptive method and qualitative research method. This article describes process of planning, organizing, actuating, and controlling in terms of disaster assistance. Furthermore, the involvement of society in the process of disaster assistance management also is discussed briefly. It generally can be concluded that the overall disaster assistance management in Sleman Regency in the case of the eruption of Merapi Volcano in 2010 could run smoothly. Furthermore, researcher also gives conclusions and suggestions that can be used to improve the quality of disaster assistance management in the future.